Evaluasi Usability Aplikasi Tiket.com Menggunakan Metode System Usability Scale (SUS) - Via Alfilaeni; Krisbiantoro, Dwi; Setyaningsih, Gustin (LPPM Universitas Potensi Utama, 2024)
This study focuses on evaluating the usability of the online ticket booking platform, Tiket.com, which despite its popularity, has received numerous negative user reviews. The primary objective of this research was to assess the platform's usability to identify areas of improvement that could enhance user experience. Utilizing the System Usability Scale (SUS) as a quantitative method to process usability data, we conducted an extensive analysis of the platform's interface and interaction features. The SUS provided a framework for assessing user satisfaction and usability efficiency. The results of this study revealed a SUS score of 55.55, which categorizes the usability level of Tiket.com as